Open Government and Social Media: A Focus on Transparency - Panom Gunawong (2018)
© 2014, © The Author(s) 2014. Social media have become new tools for the public sector to communicate with the public and to realize the idea of an open government that embraces transparency, participation, and collaboration. This article explores the adoption and use of social media applications (Facebook, Twitter, and YouTube) by Thailand’s public sector and social media’s contribution to transparency. In total, 172 public agencies representing the central, provincial, and local administration levels were investigated. Evidently, the social media applications in question have not been widely adopted and used in the Thai public sector as indicated by the small fraction of public agencies considered to be active users. Nevertheless, Facebook was found to be the only application keenly used by public agencies at all three administration levels (18 public agencies in total). An examination of their Facebook messages revealed that Facebook was employed mainly for disseminating news updates that did not actually increase the agencies’ transparency. It is thus apparent that for the Thai public sector, social media use to achieve transparency is not open to discussion. Instead, the Thai government’s first priority is to encourage public agencies to merely adopt and use social media at all, before it can focus on the most effective ways that agencies can employ such media.